Physiological, Biochemical, Epigenetic and Molecular Analyses of Wheat (Triticum aestivum) Genotypes with Contrasting Salt Tolerance - Kumar, Suresh; Beena, A. S.; Awana, Monika; Singh, Archana (Frontiers in Plant Science, 2017)
Abiotic stress exerts significant impact on plant’s growth, development and productivity. Productivity of crop plants under salt stress is lagging behind because of our limited knowledge about physiological, biochemical, epigenetic and molecular mechanisms of salt tolerance in plants. This study aimed to investigate physio-biochemical, molecular indices and defence responses of selected wheat cultivars to identify the most contrasting salt-responsive genotypes and the mechanisms associated with their differential responses. Physio-biochemical traits specifically membrane stability index, antioxidant potential, osmoprotectants and chlorophyll contents, measured at vegetative stage, were used for multivariate analysis to indentify the most contrasting genotypes. Genetic and epigenetic analyses indicated the possible mechanisms associated with differential response of the wheat genotypes under salt stress. Better antioxidant potential, membrane stability, increased accumulation of osmolytes/phytophenolics, and higher K+/Na+ ratio under 200 mM NaCl stress identified Kharchia-65 to be the most salt-tolerant cultivar. By contrast, increased MDA level, reduced soluble sugar, proline, total chlorophyll, total phenolics contents, and lower antioxidant potential in HD-2329 marked it to be sensitive to the stress. Genetic and bioinformatics analyses of HKT1;4 of contrasting genotypes (Kharchia-65 and HD-2329) revealed deletions, transitions and transversions resulting into altered structure, loss of conserved motifs (Ser-Gly-Gly-Gly and Gly-Arg) and function in salt-sensitive (HD-2329) genotype. Expression analysis of HKTs rationalized the observed responses. Epigenetic variations in cytosine methylation explained tissue- and genotype-specific differential expression of HKT2;1 and HKT2;3.